Does the adoption of peer-to-government mobile payments improve tax revenue mobilization in developing countries? - Abdoul-Akim Wandaogo; Fayçal Sawadogo; Jesse Lastunen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Developing countries need to raise sufficient tax revenue to finance development. Revenue mobilization is often hampered by limited tax compliance, weak institutions, and technical problems with tax collection. One solution to these challenges is person-to-government (P2G) mobile phone payments, adopted in a number of developing countries since the early 2000s. This study assesses the causal effect of P2G adoption on tax revenue using propensity score matching. According to the matching estimates, countries that adopt P2G services experience a 1.2-1.3 percentage point boost in direct tax revenue as a share of GDP. P2G adoption increases revenue from both corporate and personal income taxes, with larger effects on the latter. The results remain robust to matching quality tests and alternative estimation methods, including function control, two-stage least squares, and system generalized method of moments. The average treatment effects are largest among lower-middle-income countries and countries characterized by limited tax compliance and corruption control, and by low levels of urbanization and domestic credit to the private sector. The findings suggest that developing countries, particularly those with poor institutions and low levels of financial inclusion, should promote the adoption and use of mobile money services for tax transactions.
Keywords: H2; O1; O3; 330; mobile money; P2G; direct tax revenue; propensity score matching; developing countries